Association of MicroRNAs and YRNAs With Platelet Function. Issue 3 (5th February 2016) - Kaudewitz, Dorothee; Skroblin, Philipp; Bender, Lukas H.; Barwari, Temo; Willeit, Peter; Pechlaner, Raimund; Sunderland, Nicholas P.; Willeit, Karin; Morton, Allison C.; Armstrong, Paul C.; Chan, Melissa V.; Lu, Ruifang; et al.
Abstract : Rationale: : Platelets shed microRNAs (miRNAs). Plasma miRNAs change on platelet inhibition. It is unclear whether plasma miRNA levels correlate with platelet function. Objective: : To link small RNAs to platelet reactivity. Methods and Results: : Next-generation sequencing of small RNAs in plasma revealed 2 peaks at 22 to 23 and 32 to 33 nucleotides corresponding to miRNAs and YRNAs, respectively. Among YRNAs, predominantly, fragments of RNY4 and RNY5 were detected. Plasma miRNAs and YRNAs were measured in 125 patients with a history of acute coronary syndrome who had undergone detailed assessment of platelet function 30 days after the acute event. Using quantitative real-time polymerase chain reactions, 92 miRNAs were assessed in patients with acute coronary syndrome on different antiplatelet therapies. Key platelet-related miRNAs and YRNAs were correlated with platelet function tests. MiR-223 ( r p =0.28; n=121; P =0.002), miR-126 ( r p =0.22; n=121; P =0.016), and other abundant platelet miRNAs and YRNAs showed significant positive correlations with the vasodilator-stimulated phosphoprotein phosphorylation assay. YRNAs, miR-126, and miR-223 were also among the small RNAs showing the greatest dependency on platelets and strongly correlated with plasma levels of P-selectin, platelet factor 4, and platelet basic protein in the population-based Bruneck study (n=669). A single-nucleotide polymorphism that facilitates processing of pri-miR-126 to mature miR-126 accounted for a rise in circulating platelet activation markers. Inhibition of miR-126 in mice reduced platelet aggregation. MiR-126 directly and indirectly affects ADAM9 and P2Y12 receptor expression. Conclusions: : Levels of platelet-related plasma miRNAs and YRNAs correlate with platelet function tests in patients with acute coronary syndrome and platelet activation markers in the general population. Alterations in miR-126 affect platelet reactivity. Abstract : Supplemental Digital Content is available in the text.